Simulação do sistema de concentração da miscela no processo de extração de óleo de soja - Candido Neto, José Maximiano (2012)
The soybean oil processing is one of the most important sectors of agribusiness in Brazil, and has the state of Parana in third place on the Brazilian refining capacity classification. Although there is a solid knowledge about the soybeans processing, long time, it should always be efforts to find alternatives to reduce costs in the process. One way for this to occur is by the modeling and simulation process, which with means of computational experiments, it can get better results with speed and operational reliability. The general objective of this study was to define the process of soybean miscella distillation and do the modeling and simulation of this technology using HYSYS, through the direct use of available resources in the simulator or emulating the operations necessary that there is no available for direct use. The simulations were performed in HYSYS, in order to evaluate the behavior of soybean oil, soybean oil hexane miscella modeled, the individual unit operations and process as a whole. The validation and analysis of the model introduced was performed by comparing the simulations with the plant operating data, and also through the comparison with the literature. The simulation analysis showed that the model, developed in HYSYS, for soybean oil, soybean oil hexane miscella, evaporator and stripper equipments are according to the actual conditions of refinery and also with the literature. In particular, the results for the evaporator equipment were also consistent with the mathematical modeling, conducted by the balance of mass and energy equations and vapor-liquid equilibrium correlation. In summary, the objectives were made, yielding a model for the soybean oil miscella concentration step efficient and which can be used for optimization of the this step processing in a refinery.